An Examination on the Relationship between Bank Selection Criteria and the Islamic Banking Customer Satisfaction - Elkader, Moulay Omar Abd (2009)
The study examines the relationship between the bank selection criteria and the Islamic bank customer satisfaction. The bank selection criteria is directly link to the possible good perception on the good quality of service provided by the Islamic banks which also related to the high level of bank customer satisfaction in addressing the preference of the customers . The bank selection criteria is very important for their future expansion and commitment. The bank can use such information to strengthen their services, planning for capture the markets, out of many factors being theorized to have link with bank selection criteria, it is infesting to observe that today's customers ( within the context of this study) are after higher rate of return.the other factors such as Islamic principle, location and recommendation do not really effecting to bank selection criteria. It is suggestion that the Islamic bank should focus more on objective factors, such as providing competitive rate of return,in trying to attract and retain customers.